Prototype of Automatic Frequncy Control in Microhydro Power Plant with Dummy Load Based on Arduino Uno and Labview - Medilla - Kusriyanto; Handry Setya Utama; Irfan Effendi (Teknoin, 2021)
Micro hydro power plants are small-scale power plants that use hydropower as their driving force. Hydropower can come from irrigation channels, rivers or natural waterfalls, which are used by utilizing the waterfall height (head) and the amount of water discharge. The main components of this plant are the turbine and generator. The load on the micro hydro generator will affect the value of the voltage and frequency generated. This research attempts to make a micro hydro generator with automatic frequency control using dummy load in the form of inductance which is obtained using variac. The generator output voltage and current will be read by Arduino as a control center using the ZMPT101B AC voltage sensor and ACS712 current sensor. The generator output frequency is read by reading the travel time of 1(one)full wave. This research is also equipped with a variable monitoring system for micro hydro generator using Labview. From the observations of the research data, it was revealed that the frequency output of the micro hydro generator with an automatic dummy load controller was close to the value of the mesh frequency, namely 51 - 52 Hz.